Pengaruh Health Education Tentang Diet Terhadap Perubahan Tingkat Pengetahuan dan Sikap Penderita Hipertensi - Harianta, Mika; Muzakkir, Muzakkir; Darmawan, Sri (STIKES Nani Hasanuddin, 2023)
High blood pressure or hypertension is a disease characterized by an increase in blood pressure beyond normal. Hypertension often results in a dangerous situation because its existence is often not realized and often does not cause significant complaints, until complications occur in the heart, brain, kidneys, eyes, blood vessels, or other vital organs. However, hypertension is strongly influenced by the food consumed by the community. A healthy lifestyle and a healthy diet are the right choices to keep yourself free from hypertension. everything is done continuously not temporarily. Once we are careless about taking care of ourselves by following a healthy lifestyle, it is certain that we will easily get hypertension and other diseases. This study aims to determine the effect of health education on diet on changes in the level of knowledge and attitudes of hypertensive patients in the work area of ​​the Tumbang Datu Tana Toraja Health Center. This research method uses a quasi-experimental research design with a pre-post test control group design. The population in this study were people suffering from hypertension, the sample in this study was 60 respondents, the data were analyzed using the T test. researched. Explaining the Paired Sample T-Test, a significant value of 0.000 was obtained. This means that H0 is rejected because the significant value is <0.05 and Ha is accepted, with a calculated t value, namely -2.134, -21.134, -18.285, the value of t table df is .59.